Protective Effects of Java Plum (Syzygium cumini) Leaf Extract on Serum Biomarkers in Lead-Exposed Rats - Ansori, Fachrurrazi Al; Rita, Rauza Sukma; Almurdi, Almurdi (Sciences of Pharmacy, 2025)
Lead (Pb), a heavy metal recognized as a hazardous environmental toxin, triggers oxidative stress by catalyzing oxidation reactions that produce free radicals, ultimately leading to cell death. Liver cell damage due to lead can decrease serum albumin levels, while kidney damage can increase serum uric acid levels. To counteract this oxidative stress, the intake of exogenous antioxidants is necessary. Java plum (Syzygium cumini) leaves are abundant in natural antioxidants, including flavonoids and phenolic compounds. The compounds possess antioxidant potential by scavenging free radicals. The purpose of this study was to determine the effects of an extract of S. cumini on serum albumin and uric acid in rats induced with lead acetate. All treatments lasted 30 days. Testing for serum albumin and uric acid was performed using the DiaSys method. One-way ANOVA followed by the Bonferroni post hoc test revealed significant differences (p < 0.05) in serum albumin levels among the groups: the normal group (4.13 g/dL), the positive control (2.86 g/dL), and the treatment group (3.93 g/dL). Similarly, significant differences were observed in serum uric acid levels: the normal group (1.47 mg/dL), the positive control (3.14 mg/dL), and the treatment group (1.64 mg/dL). These results indicate that S. cumini extract helps mitigate the adverse effects of lead exposure on serum albumin and uric acid levels in rats. A p-value of less than 0.05 indicates that the observed differences are statistically significant and unlikely due to chance.